Changes in electrocardiographic findings after closed thoracostomy in patients with spontaneous pneumothorax - Wonjae Lee; Yoonje Lee; Changsun Kim; Hyuk Joong Choi; Bossng Kang; Tae Ho Lim; Jaehoon Oh; Hyunggoo Kang; Junghun Shin (Clinical and Experimental Emergency Medicine, 2017)
Objective We aimed to describe electrocardiographic (ECG) findings in spontaneous pneumothorax patients before and after closed thoracostomy. Methods This is a retrospective study which included patients with spontaneous pneumothorax who presented to an emergency department of a tertiary urban hospital from February 2005 to March 2015. The primary outcome was a difference in ECG findings between before and after closed thoracostomy. We specifically investigated the following ECG elements: PR, QRS, QTc, axis, ST segments, and R waves in each lead. The secondary outcomes were change in ST segment in any lead and change in axis after closed thoracostomy. Results There were two ECG elements which showed statistically significant difference after thoracostomy. With right pneumothorax volume of greater than 80%, QTc and the R waves in aVF and V5 significantly changed after thoracostomy. With left pneumothorax volume between 31% and 80%, the ST segment in V2 and the R wave in V1 significantly changed after thoracostomy. However, majority of ECG elements did not show statistically significant alteration after thoracostomy. Conclusion We found only minor changes in ECG after closed thoracostomy in spontaneous pneumothorax patients.